1977
DOI: 10.3758/bf03336961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of illumination and meter on spontaneous eyeblinks

Abstract: The hypothesis that blinking acts as a mask on visual information processing was tested. Twenty-four undergraduates listened to verbal presentations of poetry and random digits under illuminated or darkness conditions. Results indicated that the subjects' blink rates were significantly depressed during presentation of material relative to dead space paused. Results were contrary to the masking hypothesis.It has been suggested by Tarlow (1972, 1975) and Wegmann and Weber (1973) that changes in illumination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…However, research suggests that blinks are not purely following physiological necessities, but are subject to other internal and external influences, as well. Researchers have described blinking behavior as an indicator for cognitive activity (Malmstrom et al, 1977), and have found that blink timing depends on complexity and attentional demands of a task (Stern et al, 1984). Blinking has been described as an indicator for, or possibly even a component of processes around shifts in cognitive state (Oh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, research suggests that blinks are not purely following physiological necessities, but are subject to other internal and external influences, as well. Researchers have described blinking behavior as an indicator for cognitive activity (Malmstrom et al, 1977), and have found that blink timing depends on complexity and attentional demands of a task (Stern et al, 1984). Blinking has been described as an indicator for, or possibly even a component of processes around shifts in cognitive state (Oh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%